2018
DOI: 10.1111/febs.14508
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between adenylate metabolizing enzymes and AMP‐activated protein kinase

Abstract: Purine nucleotides are involved in a variety of cellular functions, such as energy storage and transfer, and signalling, in addition to being the precursors of nucleic acids and cofactors of many biochemical reactions. They can be generated through two separate pathways, the de novo biosynthesis pathway and the salvage pathway. De novo purine biosynthesis leads to the formation of IMP, from which the adenylate and guanylate pools are generated by two additional steps. The salvage pathways utilize hypoxanthine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 106 publications
(158 reference statements)
2
56
0
Order By: Relevance
“…The phosphorylation of AMPK is largely dependent on the AMP and ATP ratio [43,[46][47][48][49]. After AMP binding to the AMPK γ-subunit, the allosteric structure will change.…”
Section: A Brief Review Of Ampkmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of AMPK is largely dependent on the AMP and ATP ratio [43,[46][47][48][49]. After AMP binding to the AMPK γ-subunit, the allosteric structure will change.…”
Section: A Brief Review Of Ampkmentioning
confidence: 99%
“…Through AMP binding to site 1, the enzyme is activated. At site 3, binding of either AMP or ADP will suppress the ability of phosphatases to remove the phosphate from Thr 172 and inhibit the enzyme [9,43].The phosphorylation of AMPK is largely dependent on the AMP and ATP ratio [43,[46][47][48][49]. After AMP binding to the AMPK γ-subunit, the allosteric structure will change.…”
mentioning
confidence: 99%
“…De novo synthesis is feedback regulated by its final products adenosine 5′-monophosphate (AMP), inosine 5′-monophosphate (IMP) and guanosine 5′-monophosphate (GMP), which are allosteric inhibitors of 5-phosphoribosyl-1-pyrophosphate (PRPP) amidotransferase (PPAT) [ 5 ], while it is increased in the presence of PRPP which is both substrate and allosteric activator of the same enzyme [ 6 ] ( Figure 1 ). Conversely, the purine salvage pathway is mainly regulated by the level of expression of enzymes and their kinetic characteristics and substrate concentrations, particularly of PRPP, which is a cosubstrate for adenine, hypoxanthine, and guanine salvage [ 7 ] ( Figure 2 ). Therefore, PRPP appears to be an important regulator in common to both pathways [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the purine salvage pathway is mainly regulated by the level of expression of enzymes and their kinetic characteristics and substrate concentrations, particularly of PRPP, which is a cosubstrate for adenine, hypoxanthine, and guanine salvage [ 7 ] ( Figure 2 ). Therefore, PRPP appears to be an important regulator in common to both pathways [ 6 , 7 ]. As shown in Figure 2 , the purine salvage pathway and purine catabolism are strictly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…137,138 More importantly, phosphorylating of AMPK signaling depends on adenosine triphosphate ATP/AMP ratio to a great extent. 139,140 Interestingly, AMPK signaling expressed a dual role to protect normal brain cells from energy stress while repressing the tumor cells. 141 It has been reported that activities of glycolysis including glucose uptake, ATP levels, and lactate production were regulated by AMPK signaling in glioma cells.…”
Section: Ampk Signalingmentioning
confidence: 99%